Prevalence and genotype distribution of cervical human papilomavirus infection in the pre-vaccination era: a population-based study in the Canary Islands - Silvia De Sanjosé; Vanesa Garcia; Octavio Arencibia; Virginia Benito; Amina Lubrano; Miguel Andujar; Esther Roura; Alejandra Torres; Begoña Vega; Marta Pavcovich; Miguel Angel Sanchez; Jose Luis Trujillo; et al. (BMJ Open)
Objective National Spanish studies show that prevalence of cervical human papillomavirus (HPV) infection in the female population is increasingly frequent, with an overall estimate of 14% in women aged 18–65 years. The objective of this study is to know the prevalence and distribution of HPV types in the female population of the Canary Islands prior to the introduction of HPV vaccines and to investigate the associated clinical and sociodemographic factors.Methods Based on the Primary Health Care database, a sample of adult women (aged 18–65 years) of Gran Canaria (GC) and Tenerife (TF) stratified into nine age groups was carried out between 2002 and 2007. Women were contacted by postal letter and telephone call and were visited in their primary care centre. A clinical-epidemiological survey was completed and cervical samples were taken for cytological study and HPV detection. HPV prevalence and its 95% CI were estimated, and multivariate analyses were performed using logistic regression to identify factors associated with the infection.Results 6010 women participated in the study, 3847 from GC and 2163 from TF. The overall prevalence of HPV infection was 13.6% (CI 12.8%–14.5%) and 11.1% (CI 10.3%–11.9%) for high-risk types. The most frequent HPV type was 16 followed by types 51, 53, 31, 42 and 59. HPV types included in the nonavalent vaccine were detected in 54.1% of infected women. Factors associated with an increased risk of infection were: young ages (18–29 years), the number of sexual partners throughout life, not being married, being a smoker, and having had previous cervical lesions or genital warts.Conclusions It is confirmed that prevalence of HPV infection in the female population of the Canary Islands is high, but similar to that of Spain, HPV 16 being the most frequent genotype. The determinants of infection are consistent with those of other populations.